Infrastructure, Geographical Disadvantage, and Transport Costs. - Venables, A; Limao, N (World Bank, 1999)
December 1999 The median landlocked country has only 30 percent of the trade volume of the median coastal economy. Halving transport costs increases that trade volume by a factor of five. Improving the standard of infrastructure from that of the bottom quarter of countries to that of the median country increases trade by 50 percent. Improving infrastructure in Sub-Saharan Africa is especially important for increasing African trade. Limao and Venables use three different data sets to investigate how transport depends on geography and infrastructure. Landlocked countries have high transport costs, which can be substantially reduced by improving the quality of their infrastructure and that of transit countries. Analysis of bilateral trade data confirms the importance of infrastructure. Limao and Venables estimate the elasticity of trade flows with regard to transport costs to be high, at about -2.5. This means that: The median landlocked country has only 30 percent of the trade volume of the median coastal economy. Halving transport costs increases the volume of trade by a factor of five. Improving infrastructure from the 75th to the 50th percentile increases trade by 50 percent. Using their results and a basic gravity model to study Sub-Saharan African trade, both internally and with the rest of the world, Limao and Venables find that infrastructure problems largely explain the relatively low levels of African trade. This paper - a product of Trade, Development Research Group - is part of a larger effort in the group to investigate the effects of geography on economic performance. The authors may be contacted at ngl4@columbia.edu or aVenables@worldbank.org.